1986
DOI: 10.1351/pac198658111429
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical aspects of macrocyclic polyphosphanes and polyarsanes and of their metal complexes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Phosphinine ether macrocycles, the analogues of phosphine-ether macrocycles are designed as flexible and selective ligands in view to obtain host-guest complexes with metal cations [3]. Even if crown ethers and phosphine-ether macrocycles display interesting coordinative behavior towards metals or neutral molecules, due to optical isomerism of phosphorus atoms they posses many practical problems [5][6][7][8][9][10][11][12][13]. The aromatic character of phosphinine was demonstrated earlier by structural and magnetic criteria and also by spectral investigation [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphinine ether macrocycles, the analogues of phosphine-ether macrocycles are designed as flexible and selective ligands in view to obtain host-guest complexes with metal cations [3]. Even if crown ethers and phosphine-ether macrocycles display interesting coordinative behavior towards metals or neutral molecules, due to optical isomerism of phosphorus atoms they posses many practical problems [5][6][7][8][9][10][11][12][13]. The aromatic character of phosphinine was demonstrated earlier by structural and magnetic criteria and also by spectral investigation [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that introduction of sulfur donor atoms in these systems could modulate their complexing abilities, and several macrocycles containing a mixed phosphorus−sulfur donor set of atoms could be found in the literature. Most of them incorporate aromatic rings fused in the macrocyclic chain, but saturated ring systems containing exclusively P x S y donor set of atoms have been less developed. , The present work deals with the synthesis of the first saturated 14-membered diphosphadithia macrocycle 14P 2 S 2 (Scheme ), the separation of its cis and trans isomers, and reactions of these isomers with hydrated Ni(II) perchlorate.
1
…”
Section: Introductionmentioning
confidence: 99%
“…Von Kyba et al wurde eine ganze Reihe von Dibenzodiphospha-14hcoronanden-4i 6 synthetisiert [9]. Nicht benzoanellierte Phosphacoronanden sind nur wenige bekannt; hierher gehˆren die 18-gliedrigen Makrocyclen 7, die aufgrund der hohen Inversionsbarrieren terti‰rer Phosphine als 5 Diastereoisomere vorliegen, die von Ciampolini getrennt und charakterisiert wurden [10]. Von M‰rkl und Hoferer [11] wurden 1992 erstmals Derivate des 18hO 2 .P-Coronanden-6i 8 (RPh, cyclo-C 6 H 11 ) hergestellt.…”
unclassified